Towards a Temporal Multilevel Secure Database (TMSDB) - Haraty, Ramzi A. (2006)
Standard Relational Databases are used to store the state of reality at a single moment of time. Temporal Databases are used to store Time-Varying Data. Multilevel Secure Databases are used to securely store highly sensitive data. Each of these databases serves its purpose well, but if we were to model the temporal and sensitive aspect of the real world data, we will not be able to use any of the previously mentioned databases. Our aim here is to develop a new database model that can be used to model multilevel secure temporal data.